The Smart–Resilient–Livable–Lovable (SRLL) Model of Two Metropolitan in Sumatera - Sinatra, Fran; M. Abdi Danurja, R.A; Fenrianka J. N. D; Aprianto, Agung (UIR PRESS, 2026)
Urban development in the twenty-first century is shifting from a technocentric focus on a human-centered paradigm that emphasizes emotional bonds. The limited exploration of the interconnections among smart, resilient, and livable dimensions in shaping urban lovability presents both theoretical and empirical gaps. This study proposes and tests the Smart–Resilient–Livable–Lovable (SRLL) model to examine how technological innovation, resilience, and livability shape lovability. Utilizing a quantitative design with Structural Equation Modelling (SEM), the research compares two waterfront metropolises in Sumatera, Indonesia. Findings reveal Palembang follows a structural-integrative model, where smartness and resilience significantly enhance livability (P value 0.00), which in turn acts as a crucial mediator fostering lovability. Conversely, Bandar Lampung exhibits a social-emotional model, where smart urbanism initiatives directly build civic pride (P value 0.00) despite existing infrastructural gaps and insignificant links between livability and emotional attachment (0.077). City pride across both cities demonstrate that urban identity can grow from the soul of a city – its culture and social values – even when the body – physical infrastructure is still developing. The results offer policymakers insights for designing human-centered strategies that reconcile physical systems with the psychological well-being of residents.